Analisis Pengaruh Perubahan Penggunaan Lahan Terhadap Perubahan Suhu Permukaan pada Kawasan Sub Urban Kota Makassar: (Studi Kasus : Kecamatan Biringkanaya dan Kecamatan Tamalanea) - Taufiq Ramadhan, Muhammad; Rahman, Rahmawati; Rasyidi, Emil Salim (Journal of Urban Planning Studies, 2023)
Makassar City is a city that is experiencing growth. With growth, changes in land use that occur in a city indirectly have an impact on increasing surface temperatures. With the development of remote sensing technology, it is now possible to determine the effect of changes in land cover on changes in surface temperature in the city of Makassar. This type of research is quantitative. using satellite imagery interpretation analysis to see changes in land use and LST (Land surface temperature) analysis to measure surface temperature. The results of the study are the Makassar City Sub-Urban Area. There has been a change in land use from 2017 to 2021, namely 4.5% or 339.6 Ha and from 2017 to 2021 there has been a change in surface temperature in the Sub-Urban Area of ​​Makassar City with an average increase of 4.6°C - 5.8°C. Then, based on the results of the simple linear regression test, there is an effect of changes in land use on surface temperature in the moderate category. ah Or other related agencies, in order to reduce the impact of increasing surface temperature due to changes in land use, it is necessary to control changes in land use and the government so that they can refer to this research as material for the Makassar City spatial plan as well as strategies for program planning policies in Makassar City Sub-Urban Area.